How it ends [videorecording (DVD)] - Wein, Daryl; Lister-Jones, Zoe; Lister-Jones, Zoe; Spaeny, Cailee, 1997-; Cummings, Whitney, 1982-; Kroll, Nick; Armisen, Fred, 1966-; Wilde, Olivia; Morris, Lamorne; Hunt, Helen, 1963- (American International Pictures, an MGM Company, 2021)
In this feel-good apocalyptic comedy, freewheeling Liza scores an invite to one last wild party before the world ends. But making it there won't be easy, after her car is stolen, and the clock is ticking on her plan to tie up loose ends with friends and family. Accompanied by her younger self, Liza embarks on a hilarious journey across Los Angeles, running into an eclectic cast of characters.